Understanding health literacy for cancer prevention and care: A community-based study in rural Southwest China - Zhu, Minglan; Lachica, Toni-An B.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
Cancer remains a leading cause of mortality globally, with rural populations disproportionately affected due to limited access to healthcare services and inadequate health literacy. In China, although urban cancer incidence is higher, rural residents experience significantly higher mortality rates, reflecting disparities in early detection, treatment engagement, and health information access. This study aimed to assess the level of health literacy related to cancer prevention and treatment among rural middle-aged and older adults in northern Guizhou Province, China, and to examine variations in literacy across demographic groups. A quantitative descriptive design was employed involving 200 rural residents aged 40–75 from Zunyi City. Data were collected using a general demographic questionnaire and the validated 37-item Cancer Health Literacy Scale for Chinese Residents. Descriptive statistics were used to determine literacy levels, while Mann-Whitney U and Kruskal-Wallis tests assessed differences across demographic variables. Findings revealed intermediate levels of literacy in cancer awareness (M = 55.7), coping ability (M = 50.8), and healthy behavior beliefs (M = 48.8), with an overall score of 51.8. Treatment-related literacy also scored at intermediate levels for available information and resources, but access to healthcare professionals was low (M = 7.26). Significant differences were found by age, education level, and income (p < .05), whereas gender, marital status, family size, and current health status showed no significant variation. The study highlights moderate but uneven health literacy among rural aging populations, with critical gaps in behavioral beliefs and professional healthcare access. Health literacy is shaped by structural factors such as education and income, underscoring the need for equity-driven, community-based interventions. Strengthening culturally responsive health education and healthcare infrastructure is essential to reduce rural cancer disparities in China.